(untitled) (XXI Century. Spanish Literature and Culture, 2012)
This novel takes us back to the XIII century. It takes place in a convent where crimes have been committed. Sister Constanza is in charge of the investigation. Thus, we enter a world in which love, politics and death seem to be inextricably tangled up…The author takes the viewpoint of the different characters in order for us to understand the conflict, and the play-on-words of their dialogues captures the medieval atmosphere of this historical novel. All these elements make the plot of the story come alive as it unravels towards its “denouement”, the solution of the crimes as well as a depiction of the great king of Aragon James I, beset by personal and political problems.